Pengaruh Desain Interior terhadap Psikologis Pengguna Hotel Kapsul di Jawa Timur - Angela Lisa Kusuma; Sriti Mayang Sari; Jean Francois Poilot (Intra, 2018)
Capsule hotel started to develop in Indonesia, especially East Java, as a new form of hotel innovation that was built by considering the demand increasement of affordable backpacker hotel and limited land. This type of hotel has a very practical concept that originally designed only for resting or sleeping. That is why the room’s size in capsule hotel are smaller than the average hotel room and almost all facilities that provided are public facilities. Those not so acceptable circumstances forced the user to adapt. Whiz Capsule Trawas, Tab Capsule Hotel, and My Studio Hotel was chosen because all of them are one of the best thriving capsule hotel in East Java. This research is done to analyze the influence of interior design towards user’s psychological based on Well-Designed Space aspect by Sally Agustin with qualitative descriptive methods. The result shows that all three capsule hotel in East Java are successful in giving positive influence in creating trust (safety), comfort, and giving the space experience